Corporatism in the professions: unions, professional councils, and the state in Brazil (1930-1945) - Marco Aurélio Vannucchi (Nuevo mundo - Mundos Nuevos, 2022)
This article examines the insertion of the professions in the Brazilian corporatist apparatus created from the 1930s onwards, the construction of which was part of the conservative modernization implemented by the Varguista regime. The corporatism of the professions involved both the regulation of the professions and the representation of interests, through their official organs the unions and professional councils. The adhesion of the middle class (among whom the professions were a prestige sector) was fundamental in giving the new regime stability, due to the political importance of this social group. The article is empirically based on a broad documentary repertoire, including official statistics, documents produced by corporate entities, interviews, newspapers, and government documents.